Synbiotics and Treatment of Asthma: A Double-Blinded, Randomized, Placebo-Controlled Clinical Trial: - Maleki Mostashari, Keyvan; Hassanzad, Maryam; Ghaffaripour, Hosseinali; Emami, Habib; Rahimi limouei, Samane; Velayati, Ali Akbar (Galen Medical Journal, 2019)
Background: We examined the efficiency and safety of a specific synbiotic compound, brand name Kidilact®, in the treatment of asthma in children 12 years of age or younger. Materials and Methods: This double-blinded, randomized, placebo-controlled clinical trial was conducted in Tehran, Iran, from May 22, 2016, to May 21, 2017. One hundred children, 12 years of age or younger, who suffered from mild to moderate asthma were recruited in this study. The subjects were randomly divided into two groups; the experimental group received a sachet of Kidilact®, and the control group received a sachet of placebo once a day for six months. Both groups were compared in terms of the frequency of asthma attacks that were severe enough to require administration of fast-acting medications, the number of outpatient visits for asthma-related problems, and the frequency of hospitalization due to exacerbated symptoms of asthma. Results: There were fewer complaints of drug-induced side effects, e.g., vomiting, headache, stomachache, and diarrhea, exacerbated cough, and constipation in the experimental group than in the control group. Overall, a significantly greater number of participants in the experimental group were satisfied with the therapeutic intervention than those in the control group, as verified by the participants and their parents/guardians self-report. There was no significant difference between both groups in the frequency of asthma attacks and hospitalization due to exacerbated symptoms of asthma. The only significant difference between both groups was the count of outpatient visits. While the control group made 55 outpatient visits to the hospital, participants in the experimental group visited the hospital only 19 times (P=0.001). Conclusion: Results of our study indicates that synbiotic compound Kidilact® generally alleviates the symptoms of asthma in children of 12 years of age or younger, resulting in less frequent outpatient visits to the hospital due to asthma-related problems while rarely causing any side effects. Due to ease of use, the rarity of side effects, and their indirect positive effects on quality of life of asthmatic patients, we recommend that synbiotics be incorporated in regular treatment and management of children with asthma. [GMJ.2019;8:e1350]